Flow and stability of natural pest control services depend on complexity and crop rotation at the landscape scale. Issue 2 (25th February 2013) - Rusch, Adrien; Bommarco, Riccardo; Jonsson, Mattias; Smith, Henrik G.; Ekbom, Barbara; Landis, Doug
Summary Increasing landscape complexity can enhance biodiversity and ecosystem services in agroecosystems. However, policies based on conversion of arable land into semi‐natural habitats to increase landscape complexity and ecosystem services can be difficult to implement. Although it appears to be a promising management option, nothing is known about the effect of increasing landscape diversity through crop rotations on the delivery of ecosystem services. In this study, we examined how landscape complexity and crop rotation intensity in the landscape at different spatial scales affect the flow and the stability of natural pest control services in barley fields using manipulative cage experiments. Exclusion experiments revealed that natural enemies can have a strong impact on aphid population growth and that the delivery of pest control services is strongly dependent on the landscape context. We found that the overall level of pest control increased with landscape complexity and that this effect was independent of crop rotation intensity. In addition, the within‐field stability in pest control services increased with crop rotation intensity in the landscape, although stability in parasitism rates decreased. Multiple spatial scales analyses showed that the mean level of natural pest control was best predicted by landscape complexity at the 0·5‐km and the 1‐km spatial scales. The stability in overall pest control decreased with proportion of ley at the 2·5‐km and the 3‐km spatial scales. Synthesis and applications. Our study disentangled, for the first time, the relative effects of landscape complexity and crop rotation intensity on the delivery of an ecosystem service. We show that combined management of semi‐natural habitat and crop rotation can stabilize and enhance natural pest control in agricultural landscapes. Our findings have important implications in terms of management options to maintain and enhance ecosystem services in agroecosystems. They suggest that conservation of heterogeneous landscapes, characterized by a higher proportion of semi‐natural habitats such as pastures and relatively small fields, is essential for maintaining and enhancing effective biological control in agroecosystems.